Catalogue for Geosynthetically Stabilized Road Pavements Using 3D Finite Element Analysis - Tiwari, Aanchal; Tiwari, Ram Chandra; Jha, Prabhat Kumar; Dhakal, Dhanapati; Bhusal, Bijaya; Lamichhane, Kabin; Bhattarai, Bijaya; KC, Diwas (Journal on Transportation System and Engineering, 2026)
The current study develops a three-dimensional FEM-based for geosynthetically stabilized flexible pavements, using PLAXIS 3D simulations supported by laboratory and field data. In particular, the effect of geogrid strengthening is considered for California Bearing Ratio (CBR) ranging from 5 to 15 and the loadings varying between 5 and 30 million standard axles (msa). Based on the simulation of biaxial geogrid with axial stiffness of 700 kN/m, the analysis determines the optimal location of the grid at the subgrade-subbase interface (100% of the base thickness) in order to minimize the vertical compressive strain at the subgrade level. As a result, considerable reduction in the base thickness can be achieved with the use of the suggested arrangement; in particular, the reduction is more than 100 mm (34%) for 30 msa at the weak subgrade (CBR 5-8) and 50-90 mm (10%-18%) for 20 msa loads. A design catalog developed within the scope of the investigation can serve as a valuable guide for engineers in optimizing pavement structure and extending the life of the pavement.